Problems and Solutions in Creating a Language Environment in Public Junior High Schools in Taliwang - Muhammad Mufti Imam Suyanto; Subliansyah; Aulia Naufal (Jurnal Ilmu Pendidikan dan Sains Islam Interdisipliner, 2026)
This research aims at the problems and challenges of public secondary schools in Taliwang in creating a language environment during the process of teaching the Arabic language. Therefore, research focuses on the problems and challenges experienced by the public school and purpossing the concept, components, and strategies for creating an effective language environment based on an integrated environment. This study employs the qualitative approach in which the data are collected mainly by observation, interview, and written documents. The results of the research shows some problems facing by public schools, including minor portions of Arabic subjects taught, student’s motivation, pride in using a language other than Arabic, and the lack of a supportive language environment. This research suggested some ways to solve the problems: including setting the goal and the general vision of creating the environment, designing language activities in and outside the classroom, designing systems that ensures the language activities and their application being organized in desirable ways, preparing facilities and means that support the educational process, and cooperating with the teachers of religious sciences on designing teaching materials in the Arabic language.